Ethnomedicinal values, phenolic contents and antioxidant properties of wild culinary vegetables. (13th March 2015) - Abbasi, Arshad Mehmood; Shah, Munir H.; Li, Tong; Fu, Xiong; Guo, Xinbo; Liu, Rui Hai
Abstract: Ethnopharmacological relevance: Traditional medicines comprise a variety of health practices, approaches, knowledge, and beliefs. Documentation of traditional knowledge, estimation of total phenolics and antioxidant properties of plant species used as wild vegetables and in traditional medicines by the local communities of Lesser Himalayas-Pakistan are targeted. Materials and methods: Interviews, questionnaires, and focus group conversation with local informants were carried out to record ethno-medicinal values. Used value, percentage of people who have traditional knowledge, preference ranking and informant consensus factors were also measured. Standard analytical methods were applied to estimate phenolic contents and antioxidant properties in water and acetone extracts. Results: A total of 39 plant species used as culinary vegetables and to treat 44 different health disorders are investigated. Significant levels of use value (0.571) and preference ranking (58% PPK, PR-5) are calculated for Ficus palmata, Ficus carica and Solanum nigrum . Elevated levels of total phenolics (144.5 mg GAE/100 g, FW), and flavonoid contents (142.5 mg RtE/100 g, FW) were measured in the water extracts of Origanum vulgare, while Ficus palmata exhibits the highest flavonol contents (142.7 mg RtE/100 g, FW). Maximum DPPH activity is noted in the flowering buds of Bauhinia variegata (85.34%). However, highest values for OH − radical scavenging activity (75.12%), Fe 3+ reducing antioxidant power (54.50 µM GAE/100 g, FW), and total antioxidant capacity (180.8 µM AAE/100 g, FW) were measured in the water extracts of Origanum vulgare . Conclusion: Lesser Himalayas is a rich source of traditional cultural heritage, and plant biodiversity, which are under threat and necessitate urgent documentation. Present study is focused on the plant species used in traditional medicines and culinary vegetables as well. Preliminary determinations of phenoloic contents and antioxidant properties of various plant species were carried out. Present work will introduce new resource of medicinal and food plants, which could be used as functional food. Furthermore, phytochemical profiles, cellular based antioxidant properties, and isolation of active ingredients will be useful for consumers, and in the pharmaceutical and nutraceutical industries of the country. Graphical abstract: